ArsH protects Pseudomonas putida from oxidative damage caused by exposure to arsenic - Páez Espino, David Antonio (2020)
The two As resistance arsRBC operons of Pseudomonas putida KT2440 are followed by a downstream gene called arsH that encodes an NADPH‐dependent flavin mononucleotide reductase. In this work, we show that the arsH1 and (to a lesser extent) arsH2 genes of P. putida KT2440 strengthened its tolerance to both inorganic As(V) and As(III) and relieved the oxidative stress undergone by cells exposed to either oxyanion. Furthermore, overexpression of arsH1 and arsH2 endowed P. putida with a high tolerance to the oxidative stress caused by diamide (a drainer of metabolic NADPH) in the absence of any arsenic. To examine whether the activity of ArsH was linked to a direct action on the arsenic compounds tested, arsH1 and arsH2 genes were expressed in Escherichia coli, which has an endogenous arsRBC operon but lacks an arsH ortholog. The resulting clones both deployed a lower production of reactive oxygen species (ROS) when exposed to As salts and had a superior endurance to physiological redox insults. These results suggest that besides the claimed direct action on organoarsenicals, ArsH contributes to relieve toxicity of As species by mediating reduction of ROS produced in vivo upon exposure to the oxyanion, e.g. by generating FMNH2 to fuel ROS‐quenching activities.